Essays on Fintech and banking in China: exploring bank risk, green finance, and institutional investors - Wan, Siyu (2025)
My dissertation explores the relationship between Fintech and banks, discussing its impact from three perspectives: credit risk, green finance, and institutional investors. Chapter 2 uses data from 282 Chinese cities to examine how the level of Fintech development affects the banking industry’s credit risk in each city. The results show that Fintech development in a city significantly increases the total credit risk of the banking industry. Furthermore, the impact of Fintech on credit risk is nonlinear. It initially reduces risk, but over time, it increases. In other words, the relationship between Fintech development and credit risk follows a U-shaped curve.